Association of IL-10-Regulating MicroRNAs in Peripheral Blood Mononuclear Cells with the Pathogenesis of Autoimmune Thyroid Disease. (18th August 2017) - Takuse, Yukina; Watanabe, Mikio; Inoue, Naoya; Ozaki, Ritsuko; Ohtsu, Hiroshi; Saeki, Minori; Katsumata, Yuka; Hidaka, Yoh; Iwatani, Yoshinori
ABSTRACT: Interleukin (IL)-10 is known to suppress inflammation in autoimmune diseases. IL-10 can be regulated by miRNAs. To elucidate the involvement of miRNAs that regulate IL-10 expression with the pathogenesis of autoimmune thyroid disease (AITD), we examined the expression levels of hsa-miR-27a-3p, hsa-miR-98-5p, hsa-miR-106a-5p, and hsa-miR-223-3p in peripheral blood mononuclear cells (PBMCs) from 43 patients with Graves' disease (GD), 38 patients with Hashimoto's disease (HD), and 21 healthy volunteers. We evaluated the association between the expression levels of four miRNAs and intracellular expression of IL-10 in PBMCs from 11 healthy volunteers. We also genotyped MIR27A rs895819 G/A and MIR106A rs3747440 C/G polymorphisms, which may be related to the expression of these miRNAs in 141 patients with GD, 178 patients with HD, and 84 healthy volunteers. The expression level of hsa-miR-106a-5p was significantly higher in patients with intractable GD than in those with GD in remission ( p  = 0.0113). The expression level of hsa-miR-223-3p was significantly lower in GD than in HD and lower in patients with intractable GD than in healthy volunteers ( p  = 0.0094, 0.0340). We found a negative correlation between the expression levels of hsa-miR-98-5p and the proportions of IL-10 + cells in stimulated PBMCs from healthy volunteers ( p  = 0.0092). The G allele of the MIR27A polymorphism was significantly more frequent in patients with mild HD than in healthy volunteers ( p  = 0.0432). In conclusion, the expression levels of hsa-miR-106a-5p and hsa-miR-223-3p were associated with the pathogenesis of AITDs. hsa-miR-98-5p may negatively regulate the expression of IL-10. The functional polymorphism of MIR27A was associated with HD severity.